1972
DOI: 10.3171/jns.1972.36.5.0552
|View full text |Cite
|
Sign up to set email alerts
|

Intracranial mycotic aneurysms of extravascular origin

Abstract: ✓ Six patients with intracranial mycotic aneurysms of extravascular origin are reported. Four had aneurysms of the intracavernous portion of the internal carotid artery associated with thrombophlebitis of the cavernous sinus, and two had aneurysms of the cerebral arteries associated with meningitis. An aneurysm of this type may rupture, producing subarachnoid hemorrhage, or it may become thrombosed and decrease in size or spontaneously disappear. In some patients it may persist and develop calcification in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
23
0
1

Year Published

1985
1985
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(25 citation statements)
references
References 25 publications
1
23
0
1
Order By: Relevance
“…23 Bacterial aneurysms of the extravascular type are extremely rare in TBM, and we were able to find only two previous cases. Suwanwela et al 24 reported postmortem findings in a patient with multiple calcined aneurysms, one fusiform involving the anterior cerebral artery and three of a saccular type located in the middle, anterior, and posterior cerebral arteries. All originated at sites in which basal exudates were plentiful.…”
mentioning
confidence: 99%
“…23 Bacterial aneurysms of the extravascular type are extremely rare in TBM, and we were able to find only two previous cases. Suwanwela et al 24 reported postmortem findings in a patient with multiple calcined aneurysms, one fusiform involving the anterior cerebral artery and three of a saccular type located in the middle, anterior, and posterior cerebral arteries. All originated at sites in which basal exudates were plentiful.…”
mentioning
confidence: 99%
“…14 Meningitis due to Mycobacterium and Aspergillus is infection occasionally forms aneurysms in this fashion; however, bacterial causes remain less well described. 7 ' 16 In 1966 Ojemann et al 16 first reported angiographic evidence of aneurysm formation in distal branches of major cerebral vessels in a case of bacterial meningitis. Such lesions have since become well known but notably involve distant vessels rather than the circle of Willis.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are also extravascular sources of emboli following arterial wall infections by adjacent foci as well as cryptogenic origins of emboli that lack evidence of septic processes. 9 As a whole, bacterial aneurysms account for 2.5-6.2% of intracranial aneurysms. 10 ' 11 Although its course through the cavernous sinus would appear to render the carotid artery highly susceptible in the event of cavernous septic thrombosis, there have been only 22 7 -12 -23 documented cases of bacterial cavernous sinus aneurysms thus far, with approximately half of the cases occurring in children.…”
Section: Discussionmentioning
confidence: 99%